NEUROMARKETING: UNDERSTANDING THE SUBCONSCIOUS MIND OF CONSUMERS - Dr. Kalyanrao Kulkarni; Viveka Priya P; Baswaling; Sachin S (International Educational Journal of Science and Engineering, 2026)
Neuromarketing is an emerging interdisciplinary field that combines neuroscience, psychology, and marketing to understand consumers’ subconscious responses to marketing stimuli. Traditional marketing methods rely on self-reported data, which may not accurately capture true consumer preferences. Neuromarketing techniques such as EEG, FMRI, and eye-tracking help analyse brain activity, emotional engagement, and decision-making processes. This study explores how subconscious factors influence consumer behaviour and how businesses can leverage these insights to create effective marketing strategies. The paper also highlights ethical considerations and the future scope of neuromarketing in the digital era.